ESPERANÇA DO MUNDO: ontologia, futuro e emancipação no século 21. - SILVA, Saulo Pinto (2020)
The hope of the world is a theoretical elaboration that aims to oppose the obscurantism and resignation that dominates the global cognitive mapping. To this end, it tries to locate the constitutive issue of the failure, which operates the objective destitution of democracy and obstructs the full representation of all. Thus, the population or proletariat is the spectrum that prevents the organic unity of the social body. What we have is the explosion of revolts and conflicts within contemporary societies that maintain the reproduction of the instability of capitalism. It is in this sense that fascism appears as a popular alternative, mobilizing repressed resentment and concealing depoliticized hatred against democracy itself. What can be done? In fact, it is necessary to build the cognitive rearticulation of social oppression today, problematizing that economic exploitation, political domination and social humiliation are at variance with regard to the temporality of action. Then, we need to think that freedom without substantive equality is a trap, because it is not capable of producing truly free subjects. Capitalism, by its own inconsistent logic, expands its mechanisms of social domination to the point of establishing the exploitation of freedom, that is, the structure of feeling and emotion. So, what we have is the appearance of the depressive subject. The dead end of capitalism can only be confronted by the insistence on changing the world. Do we still have a future? The ontological need for the imagination of the future and emancipation is formulated as the first procedure to overcome defeat. We think that the Communist Idea is the immediate translation of the nomination of the future that we can wish for. But social emancipation cannot be reduced to the mere taking over of political power. It needs to go beyond failure, realizing emancipation as a new form of sensitivity and a new way of inhabiting the world. The social revolution in the 21st century is doubly the constitution of a renewed sensitive subject and the institution of a form of authentic community: communism is the political-aesthetic program of freedom and equality, happiness and joy.